Introduction to organic chemistry - Streitwieser, Andrew, Jr.; Heathcock, Clayton H. (New York : Macmillan Publishing Company, 1981)
The response to the first edition of our Introduction to organic chemistry has been gratifying. However, organic chemistry, like all science, has continued to develop at a rapid pace, and there are subjects that have matured during the last five years to a point where they deserve coverage.
1. Introduction -- 2. Electronic structure and bonding -- 3. Organic structures -- 4. Organic reactions -- 5. Alkanes -- 6. Reactions of alkanes -- 7. Stereoisomerism -- 8. Alkyl halides; nucleophilic substitution and elimination -- 9. Nuclear magnetic resonance spectroscopy -- 10. Alcohols and ethers -- 11. Alkenes -- 12. Alkynes -- 13. Aldehydes and ketones -- 14. Infrared spectroscopy -- 15. Organometallic compounds -- 16. Organic synthesis -- 17. Mass spectrometry -- 18. Carboxylic acids -- 19. Derivatives of carboxylic acids -- 20. Conjugation -- 21. Ultraviolet spectroscopy -- 22. Benzene and the aromatic ring -- 23. Electrophillic aromatic substitution -- 24. Amines -- 25. Other nitrogen functions -- 26. Sulfur and phosporaus compounds -- 27. Difunctional compounds -- 28. Carbohydrates -- 29. Amino acids, peptides, and proteins -- 30. Aromatic halides, phenols, phenyl ethers, and quinones -- 31. Polycilic aromatic hydrocarbons -- 32. Heterocyclic compounds -- 33. The chemical literature -- 34. Special topics.
Includes bibliographical references and index.
Keywords: CHEMISTRY -- ORAGNIC